The immunoproteasome controls the availability of the cardioprotective pattern recognition molecule Pentraxin3. Issue 3 (28th December 2015) - Paeschke, Anna; Possehl, Anna; Klingel, Karin; Voss, Martin; Voss, Karolin; Kespohl, Meike; Sauter, Martina; Overkleeft, Hermen S.; Althof, Nadine; Garlanda, Cecilia; Voigt, Antje
Abstract : Innate immune response pathways that involve immunoproteasome function are crucial to preserve tissue function during coxsackieviral myocarditis. We found that the catalytic activity of the LMP7 immunoproteasome subunit controls Pentraxin3 expression. Pentraxin3 is a PRR that is needed for maintaining heart tissue vitality during infection. Abstract : Cardiomyocyte death as a result of viral infection is an excellent model for dissecting the inflammatory stress response that occurs in heart tissue. We reported earlier that a specific proteasome isoform, the immunoproteasome, prevents exacerbation of coxsackievirus B3 (CVB3)‐induced myocardial destruction and preserves cell vitality in heart tissue inflammation. Following the aim to decipher molecular targets of immunoproteasome‐dependent proteolysis, we investigated the function and regulation of the soluble PRR Pentraxin3 (PTX3). We show that the ablation of PTX3 in mice aggravated CVB3‐triggered inflammatory injury of heart tissue, without having any significant effect on viral titers. Thus, there might be a role of PTX3 in preventing damage‐associated molecular pattern‐induced cell death. We found that the catalytic activity of the immunoproteasome subunit LMP7 regulates the timely availability of factors controlling PTX3 production. We report on immunoproteasome‐dependent alteration of ERK1/2 and p38MAPKs, which were both found to be involved in PTX3 expression control. Our finding of a cardioprotective function of immunoproteasome‐dependent PTX3 expression revealed a crucial mechanism of the stress‐induced damage response in myocardial inflammation. In addition to antigen presentation and cytokine production, proteolysis by the immunoproteasome can also regulate the innate immune response during viral infection.